PENGARUH DEWAN KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI PEMODERASI - Farah Widyastuti, (2023)
This study is a quantitative study aimed at understanding the influence of an independent board of commissioners and audit committees on corporate value with financial performance as a moderation variable. The population in this study is the financial sector listed on the Indonesia Stock Exchange (BEI) for the period 2019-2022. The data collected by the purposive sampling and sampling methods were 269 samples. The analysis technique used is panel data analysis. Corporate value is proxied by Price Book Value (PBV) and financial performance is proxied with Return on Asset (ROA). The results showed that the independent board of commissioners had a significant positive effect on corporate value, while the audit committee had no effect on corporate value. Financial performance does not moderate the commissioner's board's relationship with corporate value. Financial performance also does not moderate the audit committee's relationship with corporate value. Keywords: corporate value, independent commissioner, audit committee, financial performance, PBV, ROA.